Influence Boyband Korea Against Gen Z Consumptive Behavior (Case Study of Purchasing NCT 127 Concert Tickets the Unity in Jakarta) - Aprilia, Salsya Nur; Frisiska, Frisiska; Ardi Noegraha, Rosandi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The Korean Wave (Hallyu) has become a global phenomenon that influences various aspects of culture and economy, including consumption preferences. Korean boy band NCT, with its dynamic group concept and multinational members, plays an important role in spreading the influence of the Korean Wave to young audiences around the world. This study uses survey methods and data analysis to explore how NCT's influence affects Generation Z's consumption patterns, specifically in terms of purchasing merchandise, fashion products, and related digital services. The results show that Generation Z's emotional engagement with NCT significantly influences their consumptive behavior. Interactions through social media and content produced by NCT act as the main driving factors in purchasing decisions. This research provides insights into how Korean boy bands can influence consumption trends and identifies effective marketing strategies to adapt to Generation Z's preferences and behaviors. The implications of this study include the need for innovative marketing approaches and awareness of the long-term impact of the Korean Wave's influence on young consumers' consumption patterns.